2011
DOI: 10.1186/1471-244x-11-144
|View full text |Cite
|
Sign up to set email alerts
|

Massively multiplayer online role-playing games: comparing characteristics of addict vsnon-addict online recruited gamers in a French adult population

Abstract: BackgroundMassively Multiplayer Online Role-Playing Games (MMORPGs) are a very popular and enjoyable leisure activity, and there is a lack of international validated instruments to assess excessive gaming. With the growing number of gamers worldwide, adverse effects (isolation, hospitalizations, excessive use, etc.) are observed in a minority of gamers, which is a concern for society and for the scientific community. In the present study, we focused on screening gamers at potential risk of MMORPG addiction.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
153
1
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(182 citation statements)
references
References 37 publications
15
153
1
13
Order By: Relevance
“…The first is the low sample of female videogamers, as seen in other studies (Achab et al, 2011;Billieux et al, 2011;Campello de Souza, de Lima e Silva, & Roazzi, 2010). The second limitation is that there were no adult participants; the average age of videogame players is increasing, therefore research on videogame play should aim to study the older demographic as well as the younger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is the low sample of female videogamers, as seen in other studies (Achab et al, 2011;Billieux et al, 2011;Campello de Souza, de Lima e Silva, & Roazzi, 2010). The second limitation is that there were no adult participants; the average age of videogame players is increasing, therefore research on videogame play should aim to study the older demographic as well as the younger.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that we have not included a sample of videogamers in addiction treatment and that we have not identified addictive players in our sample. Finally, university students are only a part of the videogamer population (Achab et al, 2011;Collins & Freeman, 2014;Fuster et al, 2014), therefore our university sample is not representative of all videogame players.…”
Section: Discussionmentioning
confidence: 99%
“…It is hard to ignore that there is some association between violent entertainment video games and aggression, although the strong and deterministic connections often made in popular discourse (e.g., in the aftermath of school shootings) are probably not supported by the evidence [12,13]. Another issue, which is explored in research [14], addressed in clinical settings [15,16], and identified with by players themselves [17], is subjective experiences of video game "addiction. " It is usually referred to as "Problem Video Game Play" (PVGP) or by similar terms to make it possible to discuss the phenomenon without implying a position about its status as a "real" addiction [18,19].…”
mentioning
confidence: 99%
“…The main motivations for Internet gaming include social interactions and exploration [26]. The massively multiplayer on line role-playing games (MMORPG) are the most complex games, which provide the most intensive experiences of social interactions [27]. Among all types of Internet addiction, on-line game addiction shows the strongest relations with compulsive Internet use; the available study findings demonstrate that even 27.5% of players fulfil the criteria of addiction [28].…”
mentioning
confidence: 82%